Compensatory growth offsets poor condition in native trout populations. (12th September 2019) - Al‐Chokhachy, Robert; Kovach, Ryan P.; Sepulveda, Adam; Strait, Jeffrey; Shepard, Bradley B.; Muhlfeld, Clint C.
Abstract: Compensatory growth—when individuals in poor condition grow rapidly to catch up to conspecifics—may be a mechanism that allows individuals to tolerate stressful environmental conditions, both abiotic and biotic. This phenomenon has been documented fairly widely in laboratory and field experiments, but evidence for compensatory growth in the wild is scarce. Cutthroat trout ( Oncorhynchus clarkii subsp.) are cold‐water specialists that inhabit montane streams in western North America where seasonal conditions can be harsh and growth rates vary greatly among seasons. Understanding if individuals compensate for periods of reduced growth and body condition will improve understanding of the requirements of fish throughout their life‐cycle and across freshwater habitats. We quantified compensatory growth of juvenile cutthroat trout using extensive mark–recapture data from 11 stream populations (1, 125 individuals) and two subspecies inhabiting a wide range of ecological settings in the northern Rocky Mountains, U.S.A. Our objectives were to determine how growth was linked across seasons and whether individuals behaviourally compensated for depressed body condition via emigration. Fish in relatively poor condition consistently demonstrated compensatory growth in mass during subsequent seasons. In contrast, fish in relatively better condition responded with positive growth in length during the summer signalling these fish may be better suited to headwater environments; no compensatory growth in length was found during the winter. Furthermore, there was no evidence that individual condition mediated migration tendencies of fish to seek more favourable habitat. Across a wide range of environmental conditions, we found consistent empirical support for compensatory growth in mass in the wild. A critical next step is to quantify how changing abiotic and biotic conditions influence the ability of stream fishes to compensate for locally or seasonally challenging conditions, thereby affecting long‐term resiliency, viability, and adaptation in the face of changing environmental conditions.